Jordan and the Arab uprisings : regime survival and politics beyond the state - Ryan, Curtis R. (Columbia studies in Middle East politics., 2018)
Drawing upon years of fieldwork and unique access to major political figures in Jordan, Curtis Ryan unravels the unusual case of Jordan during the Arab Spring, where the country managed to avoid political upheaval amidst both regional and internal unrest.